2021
DOI: 10.1002/smll.202103645
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Cascade Nanoreactor Integrating Two‐Dimensional Pd‐Ru Nanozyme, Uricase and Red Blood Cell Membrane for Highly Efficient Hyperuricemia Treatment

Abstract: hypertension, diabetes, kidney stones, and cardiovascular diseases. [5][6][7][8] Especially, hyperuricemia promotes the development of gout in which monosodium urate crystals are deposited in joints and peripheral tissues to result in acute and chronic inflammatory arthritis. [7] Although some drugs, like allopurinol and febuxostat, have been utilized for the treatment of hyperuricemia and gout, they can only alleviate the symptoms rather than fundamentally cure the hyperuricemia due to their lack of the capab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 63 publications
0
39
0
Order By: Relevance
“…At present, nanozymes have attracted extensive attention of the researchers. [4][5][6][7][8][9] The nanocomposites with different structures have been studied as nanozymes, such as metal nanoparticle nanozymes, [10][11][12] metal alloy nanozymes, [13][14][15] and single-atom nanozymes. [16][17][18] Among these nanozymes, the single-atom nanozymes have become a research hotspot as their highly efficient and diverse enzymes-like catalytic activities.…”
mentioning
confidence: 99%
“…At present, nanozymes have attracted extensive attention of the researchers. [4][5][6][7][8][9] The nanocomposites with different structures have been studied as nanozymes, such as metal nanoparticle nanozymes, [10][11][12] metal alloy nanozymes, [13][14][15] and single-atom nanozymes. [16][17][18] Among these nanozymes, the single-atom nanozymes have become a research hotspot as their highly efficient and diverse enzymes-like catalytic activities.…”
mentioning
confidence: 99%
“…CAT‐like activity was evaluated by monitoring the generation of O 2 by the catalytic decomposition of H 2 O 2 . [ 47,48 ] As shown in Figure 4f,g, MoS 2 @Au@BSA and MoS 2 @Au NSs generated significantly higher levels of O 2 compared to the other groups; therefore, H 2 O 2 depletion was greatest with these materials, indicating remarkable CAT‐like activity. MoS 2 @Au@BSA exhibited the highest scavenging activity against the three representative ROS, and the final products of the antioxidant system were H 2 O and O 2 (Figure 4h).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to traditional urate-lowering chemical drugs, enzymes related to the degradation of urate are gaining attention, and may serve as a more direct method for hyperuricemia treatment 48,49 . Clinical data have shown that modified uricases, such as pegolase, lablipase, and pregabalin, display excellent performance in the treatment of intractable gout disease by intravenous injection; however, their duration of action in vivo is limited.…”
Section: Discussionmentioning
confidence: 99%